2011
DOI: 10.1091/mbc.e11-06-0504
|View full text |Cite
|
Sign up to set email alerts
|

Deficiencies in lamin B1 and lamin B2 cause neurodevelopmental defects and distinct nuclear shape abnormalities in neurons

Abstract: Lamin B1 is essential for neuronal migration and progenitor proliferation during the development of the cerebral cortex. The observation of distinct phenotypes of Lmnb1- and Lmnb2-knockout mice and the differences in the nuclear morphology of cortical neurons in vivo suggest that lamin B1 and lamin B2 play distinct functions in the developing brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
312
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 201 publications
(327 citation statements)
references
References 42 publications
13
312
2
Order By: Relevance
“…Immunohistochemistry studies on the cerebral cortex of Lmnb1 CS/CS embryos revealed abnormal layering of cortical neurons, but the defect was far milder than in Lmnb1 −/− embryos ( Fig. 3K) (24,25). Lmnb1 +/− mice were entirely normal and exhibited no detectable abnormalities in the brain (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Immunohistochemistry studies on the cerebral cortex of Lmnb1 CS/CS embryos revealed abnormal layering of cortical neurons, but the defect was far milder than in Lmnb1 −/− embryos ( Fig. 3K) (24,25). Lmnb1 +/− mice were entirely normal and exhibited no detectable abnormalities in the brain (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…The B-type lamins have been reported to participate in many functions within the cell nucleus, including DNA replication (21) and the formation of the mitotic spindle (22). Recently, both lamin B1 and lamin B2 have been shown to be important for neuronal migration within the developing brain (23)(24)(25)(26). A deficiency of either protein causes abnormal layering of cortical neurons (23,24).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Why such a strategy exists is unknown, but one possibility is that the precursor to lamin A, farnesyl-prelamin A, interferes with lamin B1 and lamin B2, both of which are farnesylated proteins with critical functions in the brain. In recent studies, Coffinier et al (28,29) have shown that the B-type lamins are crucial for neuronal migration and neuronal viability in the brain. It is conceivable that farnesyl-prelamin A-if produced at high levels in the brain-might compete with the B-type lamins for binding sites along the inner nuclear membrane, whereas lamin C would not.…”
Section: Discussionmentioning
confidence: 99%